2007
DOI: 10.1107/s1744309107011402
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, purification, crystallization and preliminary crystallographic analysis of selenomethionine-labelled KaiC-like protein PH0186 fromPyrococcus horikoshiiOT3

Abstract: KaiC is the central protein in the circadian-clock system of cyanobacteria. A selenomethionine-labelled KaiC-homologous protein from Pyrococcus horikoshii OT3 (PH0186; 28 kDa) was crystallized by the sitting-drop vapourdiffusion method using ethanol as a precipitant. The crystals diffracted X-rays to beyond 2.0 Å resolution using a synchrotron-radiation source. The space group of the crystals was determined to be C2, with unit-cell parameters a = 173.7, b = 51.8, c = 97.5 Å , = 122.8 . The crystal contains thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…A more extensive search of other annotated archaeal genomes indicates that KaiC homologs are widespread among all three archaeal kingdoms (i.e., Euryarchaeota, Crenarchaeota , and Nanoarchaeota ) in this domain of life, consistent with other reports (Leipe et al, 2000; Dvornyk et al, 2003; Dvornyk and Knudsen, 2005; Ming et al, 2007). Indeed, greater than half of the ~150 annotated archaeal genomes in the GenBank database have homologs to S. elongatus KaiC, most of which have a single Walker A and B domain structure (Dvornyk et al, 2003).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…A more extensive search of other annotated archaeal genomes indicates that KaiC homologs are widespread among all three archaeal kingdoms (i.e., Euryarchaeota, Crenarchaeota , and Nanoarchaeota ) in this domain of life, consistent with other reports (Leipe et al, 2000; Dvornyk et al, 2003; Dvornyk and Knudsen, 2005; Ming et al, 2007). Indeed, greater than half of the ~150 annotated archaeal genomes in the GenBank database have homologs to S. elongatus KaiC, most of which have a single Walker A and B domain structure (Dvornyk et al, 2003).…”
Section: Resultssupporting
confidence: 87%
“…Indeed, the crystal structure of a KaiC homolog from the hyperthermophilic achaeon, Pyrococcus horikoshii OT3, has been determined (Ming et al, 2007; Kang et al, 2009), yet no functional analyses have been reported to date. Given that many members of the Archaea and Bacteria inhabit overlapping ecological niches, and given the pervasiveness of horizontal gene transfer among prokaryotes (Garcia-Vallve et al, 2000; Gogarten et al, 2002; Koonin and Wolf, 2008), it is not surprising that some Archaea harbor cyanobacterial-like circadian genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the Walker motif that was shown to be most critical for KaiC hexamerization through mutagenesis (Hayashi et al, 2004) is most conserved in Archaea (Johnson and Golden, 1999). Recently KaiC protein from the Archean species Pyrococcus horikoshii OT3 was indeed shown to form hexameric rings by x-ray crystallography, which was confirmed by a gelfiltration study (Ming et al, 2007).…”
Section: Uses Of Atpmentioning
confidence: 92%
“…Numerous structural studies revealed that KaiC, purified from S. elongatus PCC 7942 or thermophilic strains, interacts homotypically (Hayashi et al, 2004; Hayashi et al, 2006; Hayashi et al, 2003; Kang et al, 2009; Ming et al, 2007; Mori et al, 2002). KaiC, when purified in the presence of ATP, forms a dumb-bell shape consisting of six KaiC monomers and 12 bound ATP molecules (Hayashi et al, 2003; Mori et al, 2002).…”
Section: The Kai-based Oscillator: Early Studiesmentioning
confidence: 99%